Information Security in Focus: Curriculum Analysis of Computer Science Courses in the Federal Network in Southeastern Brazil - Meireles, Bruno Raphael Andrade Varjão; Tomaz, Lídia Bononi Paiva (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on Cybersecurity, 2025)
In computing programs, the topic of Information Security is essential given the growing increase in cyber threats. In this context, this study investigated the presence of this topic in the curricula of courses offered by the Federal Network of Professional, Scientific, and Technological Education in Southeast Brazil, through the analysis of Pedagogical Course Projects (PCPs) of bachelor’s, technology, and licentiate programs. The results showed that the topic is significantly present in bachelor’s and technology courses but remains limited in computing licentiate programs. Nevertheless, the need to strengthen the inclusion of this theme in curricula is evident, aiming to align academic training with contemporary demands in cybersecurity.